Project handover: On proposed design, construction, completion, commissioning of Mahallah LTAT at the International Islamic University Malaysia, Gombak, Selangor Darul Ehsan / Mohamad Hairul Asri Jamaludin - Asri Jamaludin, Mohamad Hairul (Universiti Teknologi MARA, Perak, 2015)
Handover is a very important element to elaborate, therefore this report will discuss about project handing over for the building. This report was conducted for the building hostel Lembaga Tabung Angkatan Tentera (LTA T) at UIA, Gombak. The objective of this report is to know what, and how it is project hand over. It will focus on, this three segments which are before, during, and after for these project hand over. To illustrate the function of project hand over of building as an important aspect to focus on documentation and then to evaluate how far the potential of the building hand over that could fulfill the building criteria that is prescribes by the standard building requirements in the guideline. This report will also look at the project hand over management based on the guideline by producing the use of effective and to evaluate the quality to hand over project.